The Effect of Return on Assets, Debt to Equity Ratio, and Current Ratio on Earnings Management - Siska Widia Utami; Angela Dirman (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to analyze the effect of return on assets, debt-to-equity ratio, and current ratio on earnings management. The method used is quantitative research with secondary data drawn from company financial reports, using purposive sampling as the data collection technique. The data analysis used multiple linear regression analysis. The population in this study were mining companies listed on the Indonesia Stock Exchange during 2022-2024. The sample used in this study was 41 companies. The results of this study indicate that (1) return on assets have no effect on earnings management. This can be caused because companies with high ROA will maintain the company's reputation in the eyes of investors and be in the public spotlight so that the company will not carry out profit management actions that will harm the company, (2) debt-to-equity ratio have no effect on earnings management. This may be because the higher a company's debt level, the more conservative management will be in its financial and operational reporting. Management will be more cautious and less likely to take high risks through earnings management, and (3) current ratio has a positive effect on earnings management. This means that the higher the CR, the less capable the company is of maximizing its current asset management for its operations. Consequently, the company's financial performance appears less favorable to shareholders. This triggers management to engage in earnings management.